PENINGKATAN HASIL BELAJAR PKn MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE (NHT) PADA SISWA KELAS IV SD NEGERI 006 TRI MULYA JAYA KECAMATAN UKUI - Nurya’adi ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low yields of fourth grade students learn civics SD Negeri006 Tri Mulya Jaya Kecamatan Ukui. This is evidenced by the acquisition value of theaverage student learning outcomes Civics only 55 besides the percentage of students learningcompleteness sebasar 50%. This study is a class action that aims to improve student learningoutcomes Civics through the implementation of cooperative learning model NHT. This studywas conducted in two cycles, the data used in this study is the activity data of students andteachers as well as the results of PKN learn some vital lessons. Based on the results ofresearch carried out showed that the learning outcomes and activity data of teachers andstudents has increased at each cycle. It is characterized by: (a) activity increased teachers, inthe first cycle of meetings I have a 47%, in the first cycle of meetings II gained 56%, thesecond cycle of meetings I gained 69% and the second cycle II meeting gained 73%.Increased student activity data, in the first cycle of meetings I gained 50%, in the first cycle ofmeetings II gained 57%, the second cycle of meetings I gained 65% and the second cycle IImeeting gained 82%; (B) increased student learning outcomes on the basis of scores obtained55 student learning outcomes in UH I with an average of 79 learning outcomes, while theaverage student learning outcomes at the UH second cycle was 80.